MEASUREMENT OF LUNG DEAD SPACE VOLUME BY CAPNOVOLUMETRY - T.A. MIROSHKINA; S.A. SHUSTOVA (Avicenna Tajik State Medical University, 2020)
The article provides information on the lung dead space - a part of the respiratory volume that does not participate in gas exchange. The anatomical and alveolar dead spaces jointly together form the physiological dead space. The article describes methods for determining the volume of dead spaces using the capnovolumetry. The volume of physiological dead space is calculated using the C. Bohr equation. The volume of anatomical dead space can be determined using the equal area method proposed by W.S. Fowler. The volume of the alveolar dead space is the difference of volumes of the physiological and anatomical dead spaces. In pathology, the volume of the alveolar space and, consequently, physiological dead space can increase significantly. Determination of the volume of dead space is the significant criterion for diagnostic and predicting the outcome of a number of diseases.